Mapping elements distribution in carapace of Caretta caretta: A strategy for biomonitoring contamination in sea turtles?. Issue 1 (15th September 2015) - Mattei, D.; Veschetti, E.; D'Ilio, S.; Blasi, M.F.
Highlights: We analyzed 11 elements in one carapace of Caretta caretta . The distribution of the elements in carapace was studied. Mapping elements as a strategy for biomonitoring contamination in sea turtles. Some elements resulted representative for central and lateral areas of carapace. Abstract: This study analyzed the carapace distribution of Ca, Cd, Cr, Cu, Mg, Mn, Pb, Sb, U, V and Zn by GF-AAS and ICP-AES in one specimen of Caretta caretta from Mediterranean Sea. Calcium, Mg, Mn, Pb, U, Zn were mainly distributed in the central area while Cd, Cr, Cu, Sb, V in lateral areas. Cadmium, Cr, Mg, Mn, Sb, U and V were different between lateral areas. The different distribution may be related to several exposures during lifetime and/or the shell ossification during growth. Carapace may be a suitable matrix for metal biomonitoring, however, further studies are required to confirm these findings.